Cover Image. Issue 5 (24th July 2022) - Wang, Jinling; Wu, Wei; Dong, Guanping; Huang, Ke; Fu, Junfen
Abstract : The cover image is based on the Review Article Pediatric diabetes in China: Challenges and actions by Guanping Dong et al., https://doi.org/10.1111/pedi.13344 .